2018
DOI: 10.12659/msm.909162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pinocembrin Pretreatment on Connexin 43 (Cx43) Protein Expression After Rat Myocardial Ischemia-Reperfusion and Cardiac Arrhythmia

Abstract: BackgroundCardiac infarction frequently leads to arrhythmia and ischemia/reperfusion (I/R) aggravates cardiac injury. Pinocembrin can resist cerebral ischemia and decrease cardiac infarction area. This study thus generated a rat myocardial I/R model to assess the effect on ventricular rhythm and expression of gap junction connexin (Cx43).Material/MethodsMale SD rats were randomly assigned into sham, model, and pinocembrin (30 mg/kg) pretreatment groups (N=15 each). The I/R model was generated by ligation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Pinocembrin could also regulate the ion channels (e.g. Na + -K + ATPase, Ca 2+ -Mg 2+ ATPase, and Kir2.1), as well as the gap junction [e.g., Connexin (Cx) 43 Cx43] in myocardial tissues (Zhang et al, 2018). Moreover, our latest study demonstrated that pinocembrin could attenuate autonomic dysfunction and cardiac arrhythmias in myocardial infarction (MI) rats, confirming the cardioprotection of pinocembrin (Ye et al, 2019b).…”
Section: Introductionsupporting
confidence: 59%
“…Pinocembrin could also regulate the ion channels (e.g. Na + -K + ATPase, Ca 2+ -Mg 2+ ATPase, and Kir2.1), as well as the gap junction [e.g., Connexin (Cx) 43 Cx43] in myocardial tissues (Zhang et al, 2018). Moreover, our latest study demonstrated that pinocembrin could attenuate autonomic dysfunction and cardiac arrhythmias in myocardial infarction (MI) rats, confirming the cardioprotection of pinocembrin (Ye et al, 2019b).…”
Section: Introductionsupporting
confidence: 59%
“…In the last decade, compelling evidence has indicated a potential role for Cx43 in cardioprotection [49][50][51]. The role of Cx43 in cardiac I/R injury has been extensively investigated in both ex vivo [38,50,[52][53][54] and in vivo models [50,55,56]. The Langendorff perfusion system has proven very useful to explore the impact of ischemic conditions on Cx43 expression, PTMs and cellular localization [52,[57][58][59], while the LAD ligation model of regional I/R injury has been widely used to study the effects of pharmacological interventions involving Cx43 [54][55][56].…”
Section: Cx43 Gap Junction-and Hemi-channels and Cardiac I/r Injurymentioning
confidence: 99%
“…Pinocembrin induces ER stress via the inositol-requiring endonuclease 1 α/X-box binding protein 1 pathway and then triggers caspase-12/-4 mediated apoptosis by suppressing autophagy through the activation of PI3K/Akt/mTOR pathway [9]. Pinocembrin also reduced ventricular arrhythmias in I/R rats by enhancing Na + -K + ATPase and Ca 2+ -Mg 2+ ATPase activity and up-regulating Cx43 and Kir2.1 protein expression [61].…”
Section: Pharmacological Effects Of Pinocembrinmentioning
confidence: 99%